PENGARUH PENGGUNAAN MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPS DI KELAS IV SD - Aswin, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research aimed to analyze the effectiveness of Example Non Example Model through students learning outcomes in learning Social Sciences in fourth grade SDN 16 Pontianak Utara. This research used an experimental method with quasy-experimental design with research programme nonequivalent control group design. The population in this research were all fourth grade students of SDN 16 Pontianak Utara. The samples of this research that the experimental class students that amounted to 33 people and control classes totaling 29 people. Data collector in the form of multiple choice tests totaling 50 questions. The average yield post-test in control class 57.16 and the average post-test experimental class 72.85. Calculation of effect size of 1.35 with a very high category. The results of the t-test of 6.3659 to ttabel 2.0424, means thitung> ttabel (6.3659> 2.0424) then Ha accepted, meaning that there are significant effectiveness of Example Non Example Model through students learning outcomes in learning Social Sciences in fourth grade SDN 16 Pontianak Utara. Keywords: Effectiveness, Example Non Example Model, Learning Outcomes. Â